2014
DOI: 10.1097/pcc.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

Greater Fluctuations in Serum Sodium Levels Are Associated With Increased Mortality in Children With Externalized Ventriculostomy Drains in a PICU*

Abstract: Objective Dysnatremia is common in critically ill children due to disruption of hormonal homeostasis. Children with brain injury are at risk for SIADH, cerebral salt wasting and sodium losses due to externalized ventricular drain (EVD) placement. We hypothesized that among pediatric intensive care unit (PICU) patients managed with an EVD, hyponatremia is common, hyponatremia is associated with seizures and in-hospital mortality, and greater sodium fluctuations are associated with in-hospital mortality. Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…The association of sodium fluctuations and mortality has been shown in a large cohort of adult surgical ICU patients [9] and in pediatric ICU patients who require externalized ventriculostomy drains [13]. Our study validates the findings of an independent association between sodium fluctuations and mortality, and also the association between degree of sodium fluctuation and an increased odds of in-hospital mortality.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The association of sodium fluctuations and mortality has been shown in a large cohort of adult surgical ICU patients [9] and in pediatric ICU patients who require externalized ventriculostomy drains [13]. Our study validates the findings of an independent association between sodium fluctuations and mortality, and also the association between degree of sodium fluctuation and an increased odds of in-hospital mortality.…”
Section: Discussionsupporting
confidence: 87%
“…A recent study by Sakr and colleagues [9] found an independent association between sodium fluctuations and mortality, even in patients who remained within the reference range throughout their ICU stay. The association of sodium fluctuations and mortality has been validated in only one other study, in a subgroup of a pediatric population requiring externalized ventricular drains [13]. …”
Section: Introductionmentioning
confidence: 99%
“…As rightly pointed out by Fante et al, we did not observe a statistically significant association between hyponatremia and seizures or hospital mortality (2). This is counter to what has been previously published by others (35).…”
supporting
confidence: 54%
“…Both hyponatremia and hypernatremia have been widely associated with increased morbidity and mortality. Furthermore, as suggested by recently published studies, even small fluctuations in serum Na levels have been associated with a significant increase of in-hospital mortality [5][6][7][8].…”
Section: Introductionmentioning
confidence: 74%